Catch Trend and Stock Assessment of Hilsa Tenualosa ilisha Using Digital Image Measured Length‐Frequency Data. Issue 4 (11th July 2018) - Rahman, Mohammad Jalilur; Wahab, Md. Abdul; Amin, S. M. Nurul; Nahiduzzaman, Md.; Romano, Nicholas
Abstract: The annual global average catch shares of the anadromous Hilsa Tenualosa ilisha of Bangladesh increased rapidly from 74.5% all through 1984–2013 to 86.7% during the 2010–2015 periods. With a few exceptions, an increasing trend of Hilsa production over the last three decades was found in Bangladesh. Initially three options incorporating digital image measurements were compared to determine the best method for obtaining accurate length data. The length‐frequency data measured from digital images showed that Hilsa have a moderate growth rate ( K = 0.90 year −1 ) of up to 58.70 cm ( L ) TL. High fishing mortality ( F = 2.83 year −1 ) and exploitation level ( E = 0.67) suggest a slight overexploitation of the Hilsa fishery; the maximum sustainable yield (MSY) was estimated at 526, 000 metric tons/year if the recommended TL at first capture ( L c ) of 27 cm is adhered to. The present annual Hilsa catch is about 496, 417 metric tons, which indicates the potential benefit of achieving MSY through sustainable fisheries management by regulating mesh size of nets and protecting brood fish. Size distribution of Hilsa within sanctuaries revealed a remarkable presence of juvenile fish during February–March in some areas, which suggests a need to readjust the fishing ban period from March–April to February–March. More fisheries management is necessary to reduce the exploitation level of Hilsa by 17% and at the same time increase the allowable L c to potentially increase the MSY and CPUE.